A new caprellid species (Crustacea: Amphipoda: Senticaudata) from Brazil - Ros, Macarena; Lacerda, Mariana B.; Guerra-García, José M. (Zootaxa, 2017)
A new species of caprellid, Pseudaeginella arraialensis, is described from Arraial do Cabo, Rio de Janeiro, Brazil. Abundant material was collected in Praia do Forno, associated to hydroids and algae of natural rocky substrata and fouling communities of artificial floating structures. The new species can be distinguished easily from the remaining species in the genus mainly by the pattern of dorsal projections, and by the setose antennae and gnathopod 2 in males. The dietary analysis revealed that the species is omnivorous, with a high contribution of small crustaceans in its diet. Detailed figures showing ontogenetic development and intraspecific variation of P. arraialensis are also included.